2021
DOI: 10.3389/fendo.2020.602535
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Late-Onset Congenital Adrenal Hyperplasia and Acute Covid-19 Infection in a Pregnant Woman: Multidisciplinary Management

Abstract: BackgroundThe impact of the Covid-19 infection on patients with chronic endocrine disease is not fully known. We describe here the first case of a pregnant woman with Covid-19 acute infection and non-classical congenital adrenal hyperplasia (NCAH).Case descriptionA woman at 36 weeks of gestation was referred to our Maternity Hospital for premature rupture of membranes (PROM). Her medical history was positive for NCAH on chronic steroid replacement till the age of 17 years (cortisone acetate and dexamethasone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The special psychological and physiological changes during pregnancy make this group more susceptible, which will cause harm to the intrauterine growth and development of the fetus, and should be paid attention to. Most of the previous studies on the impact of COVID-19 on pregnant women have focused on case reports, such as passive immunity in COVID-19 patients during pregnancy ( Toner et al, 2020 ); COVID-19 patients with multiple systems inflammatory syndrome during pregnancy ( Gulersen et al, 2021 ) , and vertical transmission of COVID-19 patients during pregnancy ( Sukhikh et al, 2021 ), acute infection and other reports ( Giavoli et al, 2020 ). Studies have also pointed out the analysis of the status of new coronary pneumonia in pregnant women ( Fox and Melka, 2020 ), the clinical manifestations of COVID-19 patients during pregnancy ( Sabharwal et al, 2021 ), and the study of adverse childbirth outcomes ( Sun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The special psychological and physiological changes during pregnancy make this group more susceptible, which will cause harm to the intrauterine growth and development of the fetus, and should be paid attention to. Most of the previous studies on the impact of COVID-19 on pregnant women have focused on case reports, such as passive immunity in COVID-19 patients during pregnancy ( Toner et al, 2020 ); COVID-19 patients with multiple systems inflammatory syndrome during pregnancy ( Gulersen et al, 2021 ) , and vertical transmission of COVID-19 patients during pregnancy ( Sukhikh et al, 2021 ), acute infection and other reports ( Giavoli et al, 2020 ). Studies have also pointed out the analysis of the status of new coronary pneumonia in pregnant women ( Fox and Melka, 2020 ), the clinical manifestations of COVID-19 patients during pregnancy ( Sabharwal et al, 2021 ), and the study of adverse childbirth outcomes ( Sun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our analysis, six pregnant women went into spontaneous premature labor 12,14,[16][17][18][19]22 , two had premature rupture of membranes 18,19 and one had a placenta abruption 20 . Three evolved to spontaneous vaginal delivery 13,17,18 and, among them, only one received intrapartum oxytocin 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Concerning to neonatal mortality, according to Allotey et al 26 , rates are low in women confirmed or suspected for Covid-19, despite of an increased risk of neonatal ICU admission. A total of eleven newborns remained healthy after delivery 6,16,17,19,20,22,24,25 , and of these, there were triplets with a positive nasopharyngeal swab for SARS-CoV-2 16 .…”
Section: Resultsmentioning
confidence: 99%